Study of effect of peritoneal dialysis and cell therapy on syndrome of intestinal insufficiency in necrotizing pancreatitis - KebkaloA.B. (Medičnì Perspektivi)
The aim was to prove the effectiveness of the use of methods of detoxification and stimulation of reparative processes in the complex treat¬ment of patients with intestinal insufficiency syndrome with necrotizing pancreatitis. For detoxification in patients with necrotizing pancreatitis, we chose the method of fractional peritoneal dialysis, that represents periodic injection of the dosed volumes of dialysate into abdominal cavity, which is removed after a fixed period of time. For stimulation of detoxication pro¬perties of liver and reparative processes in the body, stem cells of cord blood were used. Cord blood at a dose of 10 ml was slowly injected intravenously with dilution with physiological solution 1:1 starting from 2-3 days after the beginning of disease within 3-5 days. Intraabdominal pressure was measured in the bladder using tonometer of low pressure. Material for bacteriological examination was taken during puncture intervention under ultrasound control. Identification of pure culture was performed by the staging of "motley series", and also by bacteriological analyzer VITEK-2. To study the effectiveness of the combined methods of detoxification in toxemia phase, patients with necrotizing pancreatitis were divided into three groups. The control group consisted of 30 patients with necrotizing pancreatitis treated with standard detoxification. The group of comparison consisted of 25 patients with necrotizing pancreatitis, only with fractional peritoneal dialysis, only, and a basic group of 15 patients with the combined use of fractional peritoneal dialysis and the stem cells of cord blood. Basing on this study it was found that in patients of control group intestinal paresis was during 5,82±0,2 days. In application of fractional peritoneal dialysis length of intestinal paresis was 2,82±0,9 days, and in the group with complex treatment including cell therapy 2,39 ± 0,7 days. The combined use of fractional peritoneal dialysis and the stem cell of cord blood results in more rapid decrease of intraabdominal pressure by 2,43 (p<0,01) times and reduce of intestinal paresis in patients with necrotizing pancreatitis in phase of enzyme toxemia. In combined use of fractional peritoneal dialysis and transplantation of stem cells of cord blood decrease in the number of infectious complications by 1,7 (p<0,05) times compared to the control group is most marked.